SEGREGASI SOSIAL, PENDIDIKAN ISLAM MULTIKULTURALISME MEDIA RESOLUSI KONFLIK UNTUK HARMONI - Himayatul, Himayatul Izzati (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Abstract This article will discuss about social segregation, Islamic education as a media to neutralize conflict. Multicultural Islamic education must be understood as a process of civilizing the principles of democracy, equality and justice oriented towards strengthening human values, togetherness, and peace; and develop an attitude of accepting and appreciating any diversity based on the Qur'an and hadith. Education is part of the duties of the human caliphate that must be carried out responsibly. Islamic religious education can be used as a fairly effective medium, to give birth to a generation of people who have awareness of multiculturalism. The writing of this article uses qualitative methods in the form of library research. The data sources used in this study are literature, both from books and Islamic education journals that have relevance to social segregation and multicultural education. Data analysis was carried out in two stages, the first was text content analysis and social context analysis. The cultivation of multicultural values ​​must start from the family, school, and community by involving all components, which is expected to be able to prevent friction between ethnic groups and between social groups that can lead to social conflict. Thus, everyone must realize that he or she was born from a different cultural background, customs, ethnicity, and religion. Difference is sunnatullah that must be accepted by everyone. Thus, it will give birth to a sense of respect and tolerance among fellow human beings.